Nasal changes associated with exercise in athletes: systematic review. Issue 3 (18th January 2018) - Surda, P; Walker, A; Limpens, J; Fokkens, W; Putala, M
Abstract: Background: The prevalence of rhinitis in athletes has frequently been studied in combination with asthma, but the impact of exercise on the paracrine and secretory functions of nasal mucosa is less well established. This systematic review aimed to examine the effect of exercise on nasal mucosa in elite athletes. Method: A systematic search of Medline, Embase and the non-Medline subset of PubMed, from inception to 8th March 2016, was performed to identify studies on rhinitis in athletes. Results: Of the 373 identified unique articles, a total of 8 studies satisfied the criteria for this review. Conclusion: There is no evidence in the existing literature that indicates a reduction in nasal airway induced by exercise. Olfaction and mucociliary transport time are affected in swimmers, which can likely be attributed to chlorine irritation and which resolves with training cessation. Short-term strenuous exercise may trigger changes in cytology and prolonged mucociliary transport time, which also resolve quickly with rest.